A formação do Supervisor Escolar em encontros colaborativos e de parceria com outros gestores educacionais - Silva, João Batista Pires da (2012)
This investigation aims at linguistically analyzing the professional in-service education of a school supervisor and of the managerial team of a local municipal school in São Paulo in interactions that were established within reflective conversations which discussed the prescriptions found in Governmental Orders that rule over the specificities of the School Supervisor s job in terms of their advisory and guidance activity with school management. In other words, the dissertation analyzes the extent to which the interaction loci established for the participants education are meaningful for the researcher-supervisor in his interactions with a collaborating supervisor, and later with the school principal and pedagogical coordinator of the municipal school. Theoretically speaking, the dissertation is based on Libâneo s (2008) and Lück s (2008) concepts of educational management as paradigms that seek cohesion of the pedagogical activity as well as a greater participation from the collectivity in decision making. Furthermore, the role of the school supervisor in terms of actions that relate educational policies to their educating actions is also discussed from the viewpoints of Rangel (1997 and 2011), Paro (2011), Evangelista and Freire (2011), Giancaterino (2010), Ferreira (2008) and Carvalho and Oliveira (2012). The research is also supported on the Critical Pedagogy (FREIRE, 1975 and 2001) and on the Socio-Cultural-Historical Theory, with a focus on aspects such as mediation and zone of proximal development (VYGOTSKY, 1996 and 2000), on language that is seen as an invaluable tool, that is intrinsically ideological (Bakhtin, 2003 e 2004), necessary for the awareness raising of educational professional by means of a dialogical practice. The used methodology was that of Critical Research of Collaboration (MAGALHÃES, 2004), since it assumes the need for social and educational transformation by means of reflected actions taken in partnership with the management team. Data was generated in: (1) two educational meetings, which are here called reflective conversations, with the researcher-supervisor and a collaborating supervisor; and (2) a meeting, another reflective conversation with the researcher-supervisor, the principal and a pedagogical coordinator of a public municipal school. Data were analyzed from the viewpoints of Kerbrat-Orecchioni (2006), as well as with the discourse analysis categories by Orsolini (2005), and the interaction analyses discussed by Pontecorvo (2005) and utterance responsibility, according to Adam (2011). This investigation is justified by the growing concern with the education of the school management team in face of the also growing social and political transformations worldwide, and more specifically, the Brazilian transformations which took place during the twentieth century. Throughout the research, I have concluded that the education of the school supervisor is essential for the development of an activity that is committed with political and social matters, understanding these professionals as rebuilders of institutional educational objectives that are useful for the improvement of didactic-pedagogical practices in schools. By thinking about these matters as starting points, the investigation is carried out, analyzing the distance between the job that is prescribed and that which is carried out by the managerial team in terms of the implementation of actions that seek to develop and design school projects